Tlingit seal hunters in canoe, Alaska, ca. 1898 - Miller, N. B.
Two men in a canoe hunt seals; one is paddling, the other is standing in the bow preparing to throw a spear, ca. 1898-1899 Note from unidentified source: Indian hunter throwing spear at seal